2017
DOI: 10.1016/j.bbamcr.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel peptide motifs in the serpin maspin that affect vascular smooth muscle cell function

Abstract: Identification of novel peptide motifs in the serpin maspin that affect vascular smooth muscle cell function, BBAMolecular Cell Research (2016Research ( ), doi:10.1016Research ( /j.bbamcr.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Gene Ontology (GO) analysis identified that the major discriminators between atherosclerotic and non-atherosclerotic patients were those involved with superoxide radical generation, and particularly superoxide dismutase (SOD1) overexpression. An additional protein uncovered in this study was the SERPIN family-related protein SERPINE2, which is note-worthy in that members of the SERPIN family have recently been identified as key regulators of VSMC migration, adhesion, signal transduction and proliferation, linking atherogenic stimuli and VSMC dysfunction [ 30 , 31 ]. Ang II exerts cellular damage via the production of reactive oxygen species in VSMC and its paracrine effects on other cells in proximity in an NAD(P)H-dependent mechanism [ 32 ].…”
Section: Relationships Between Ras Inflammation and Hyperlipidemmentioning
confidence: 99%
“…Gene Ontology (GO) analysis identified that the major discriminators between atherosclerotic and non-atherosclerotic patients were those involved with superoxide radical generation, and particularly superoxide dismutase (SOD1) overexpression. An additional protein uncovered in this study was the SERPIN family-related protein SERPINE2, which is note-worthy in that members of the SERPIN family have recently been identified as key regulators of VSMC migration, adhesion, signal transduction and proliferation, linking atherogenic stimuli and VSMC dysfunction [ 30 , 31 ]. Ang II exerts cellular damage via the production of reactive oxygen species in VSMC and its paracrine effects on other cells in proximity in an NAD(P)H-dependent mechanism [ 32 ].…”
Section: Relationships Between Ras Inflammation and Hyperlipidemmentioning
confidence: 99%